2022
DOI: 10.1021/jacs.2c07781
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Recycling of Polyethylene by Tandem Catalytic Conversion to Propylene

Abstract: Although polyethylene (PE) and polypropylene (PP) are by far the world's largest volume plastics, only a tiny fraction of these energy-rich polyolefins are currently recycled. Depolymerization of PE to its constituent monomer, ethylene, is highly endothermic and conventionally accessible only through unselective, high-temperature pyrolysis. Here, we provide experimental demonstrations of our recently proposed tandem catalysis strategy, which uses ethylene to convert PE to propylene, the commodity monomer used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 37 publications
0
94
0
Order By: Relevance
“…Abu-Omar and co-workers incorporated unsaturation into commercial polyethylene via stoichiometric bromination and dehydrobromination, followed by ethenolysis to form low-molecular-weight divinyl-terminated polyethylene as value-added products (Figure c) . Recently, Hartwig and co-workers, and Guironnet, Scott and co-workers catalytically deconstructed polyethylene through transfer dehydrogenation, isomerization, and metathesis into propylene (Figure d). , In this work, dehydrogenated HDPE was used to develop recyclable-by-design polyethylene-like materials from hard-to-recycle waste HDPE (Figure ).…”
mentioning
confidence: 99%
“…Abu-Omar and co-workers incorporated unsaturation into commercial polyethylene via stoichiometric bromination and dehydrobromination, followed by ethenolysis to form low-molecular-weight divinyl-terminated polyethylene as value-added products (Figure c) . Recently, Hartwig and co-workers, and Guironnet, Scott and co-workers catalytically deconstructed polyethylene through transfer dehydrogenation, isomerization, and metathesis into propylene (Figure d). , In this work, dehydrogenated HDPE was used to develop recyclable-by-design polyethylene-like materials from hard-to-recycle waste HDPE (Figure ).…”
mentioning
confidence: 99%
“…For example, Guironnet and Peters proposed a kinetic model of a new polyethylene conversion approach which consists of tandem olefin metathesis and double-bond isomerization for selective depolymerization to propylene . Excitingly, this simulated path was recently successfully verified by Conk et al using well-designed homogeneous catalytic systems or by Wang et al using a multifunctional heterogeneous catalyst, respectively . In Wang’s work, they use Pt/Al 2 O 3 as a dehydrogenation catalyst and commercial MTO catalyst as an olefin metathesis catalyst.…”
Section: Discussionmentioning
confidence: 99%
“…Further research could focus on ways to perform this reaction in a continuous fashion. A semi-continuous process was already shown to be possible by Wang et al, [14] flowing ethylene continuously through the reactor, leading to a propylene yield of 27 % over 5 h. These authors also explore a heterogeneous isomerization/metathesis catalyst system in combination with a dehydrogenation catalyst in one pot, which is more stable compared to the two-step homoge- neous system but at much decreased reaction rates. In addition, it is demonstrated that existing alkenes remaining from termination of PE, polymerized by a Philips catalyst, can be utilized as starting materials for the isomerization/ metathesis step (Figure 1A).…”
mentioning
confidence: 99%
“…In addition, it is demonstrated that existing alkenes remaining from termination of PE, polymerized by a Philips catalyst, can be utilized as starting materials for the isomerization/ metathesis step (Figure 1A). [14] Finally, compatibility with contaminated and mixed plastic waste streams also needs to receive further research attention. While Conk et al successfully applied the tandem depolymerization to some waste items, other possibly multilayer food packaging resisted dehydrogenation.…”
mentioning
confidence: 99%